To Evaluate the Different Rapid Screening Tests for Diagnosis of Leptospirosis - Panwala, Tanvi (J Clin Diagn Res, 2015)
Introduction: Leptospirosis is an acute febrile disease, in tropical and sub-tropical regions of world. It has been under-reported in India, due to presence of non-specific symptoms and unavailability of appropriate laboratory diagnostic facilities in most part of the country. The diagnosis of leptospirosis is usually based on demonstration of antibodies by different serological tests. Aim: The present study aims to evaluate and compare commercially available rapid test. Design and Settings: Case control study. Materials and Methods: Three screening tests (Leptocheck WB, Latex agglutination test and SD leptospira) were compared by using 100 serum samples randomly obtained from clinical cases of Leptospirosis admitted in new civil hospital, Surat, Gujarat. All the patients with acute Leptospirosis were included in this 4-months pilot study from July 2011 to October 2011. All the results were compared with IgM ELISA and MAT for confirmation of diagnosis. Results: Leptocheck WB, Latex agglutination test and SD leptospira had sensitivities of 84.8%, 84.8% and 72.7% & specificities of 37.3%, 71.2% and 71.2% respectively as compared to MAT. Leptocheck WB, Latex agglutination test and SD leptospira had sensitivities of 90.7%, 89.7% and 53.7% & specificities of 93.4%, 90.9% and 60% respectively as compared to IgM ELISA. Conclusion: Latex agglutination test kit and Leptocheck WB were found to be highly sensitive and specific. Neither of these tests require specialized equipment, and could be performed in peripheral laboratories with relatively little expertise.